VALUE OF LOCAL ADMINISTRATION OF TRANEXAMIC ACID IN CARDIAC SURGERY WITH CARDIOPULMONARY BYPASS - S. I. Sergey; A. G. Yavorovskiy; T. P. Zyulyaeva; O. V. Dymova (Вестник анестезиологии и реаниматологии)
Peri-operative bleeding in surgeries with cardiopulmonary bypass results in the increase of post-operative complications and mortality. Fibrinolysis hyperactivation is the common cause of non-operative bleeding. Materials and methods. 60 patients who had cardiac surgery with cardiopulmonary bypass were enrolled into the study. The antifibrinolytic agent (tranexamic acid) was administered to all patients: 32 patients (TA1) received an intravenous loading dose of tranexamic acid basing on 15 mg/kg during 20 min. with the consequent infusion of 1 mg/(kg × h-1) + 500 mg during cardiopulmonary bypass; 28 patients (TA2) received intravenous loading dose of tranexamic acid (15 mg/kg for 20 minutes) with the consequent infusion of 1 mg/(kg × h-1) + 500 mg during cardiopulmonary bypass + 1000 mg administered into the pericardial cavity and sternum before its closure. The peri-operative blood loss and volume of blood transfusion (erythrocyte suspension, fresh frozen plasma, platelet concentrate) were assessed. Results. Intra-operative blood loss made 815 (800–862) ml in TA1 group and 700 (650–735) ml in TA2 group. The volume of the post-operative blood loss in TA2 group was confidently lower compared to TA1 group: 170 (100–240) ml versus 275 (180–307) ml respectively. The frequency of erythrocyte suspension transfusion in the post-operative period did not differ significantly and the frequency of fresh frozen plasma transfusion was 2.5 lower in TA2 group compared to TA1 group. Conclusions. Blood-saving effect of the system administration of tranexamic acid is enhanced by local its administration into the pericardial cavity and sternum.